In complete SCI patients, long-term functional electrical stimulation of permanent denervated muscles increases epidermis thickness. (3rd April 2018) - Albertin, Giovanna; Hofer, Christian; Zampieri, Sandra; Vogelauer, Michael; Löfler, Stefan; Ravara, Barbara; Guidolin, Diego; Fede, Caterina; Incendi, Damiana; Porzionato, Andrea; De Caro, Raffaele; Baba, Alfonc; et al.
Abstract: Our studies have shown that atrophic Quadriceps muscles from spinal cord injury patients suffering with permanent denervation-induced atrophy and degeneration of muscle fibers, were almost completely rescued to normal size after two years of home-based functional electrical stimulation (h-bFES). Because we used surface electrodes to stimulate the muscle, we wanted to know how the skin was affected by the treatments. Here, we report preliminary data from histological morphometry of Hematoxylin-Eosin-stained paraffin-embedded skin sections harvested from the legs of three SCI patients before and after two years of h-bFES. Despite the heterogeneity of gender and time from SCI, comparing pre vs post h-bFES in these three SCI patients, the data show that: (1) In one subject skin biopsies from both the right and left leg experienced a statistically significant increase in thickness of the epidermis after two years of H-bFES; (2) In the other two subjects, one leg showed a significant increase in epidermis thickness, while in the other leg there was either small positive or negative non-significant changes in epidermis thickness; and (3) more importantly, comparison of grouped data from the three subjects shows that there was a significant 28% increase in the thickness of the epidermis in response to two years of h-bFES rehabilitation. In conclusion, the three educational cases show a long-term positive modulation of epidermis thickness after two years of h-bFES, thus extending to skin the positive results previously demonstrated in skeletal muscle, specifically, a substantial recovery of muscle mass and contractile function after long-term h-bFES.